The safety and feasibility of laparoscopic anatomical left hemihepatectomy along the middle hepatic vein from the head side approach - Li, Wen; Fang, Lu; Huang, Yong (Frontiers in Oncology, 2024)
Background: Laparoscopic left hemihepatectomy (LLH) is commonly used for benign and malignant left liver lesions. We compared the benefits and drawbacks of LLH from the head side approach (LLHH) with those of conventional laparoscopic left hemihepatectomy (CLLH). This study was conducted to investigate the safety and feasibility of LLHH by comparing it with CLLH. Methods: Herein, 94 patients with tumor or hepatolithiasis who underwent LLHH (n = 39) and CLLH (n = 55) between January 2016 and January 2023 were included. Preoperative features, intraoperative details, and postoperative outcomes were compared between the two groups. Results: For hepatolithiasis, patients who underwent LLHH exhibited shorter operative time (P = 0.035) and less blood loss (P = 0.023) than those who underwent CLLH. However, for tumors, patients undergoing LLHH only showed shorter operative time (P = 0.046) than those undergoing CLLH. Moreover, no statistically significant differences in hospital stay, transfusion, hospital expenses, postoperative white blood cell count (WBC), alanine aminotransferase (ALT), and aspartate aminotransferase (AST) were observed between the two groups (P > 0.05) for tumor or hepatolithiasis. For HCC, no differences in both overall survival (P = 0.532) and disease-free survival (P = 0.274) were observed between both groups. Conclusions: LLHH is a safe and feasible surgical procedure for tumors or hepatolithiasis of the left liver.